Brand Image or Price? Tracing the Path of Satisfaction to Telkomsel Consumer Loyalty - Maftuhah Nurrahmi; Kamisah Supian (Faculty of Economics and Business, Universitas Negeri Yogyakarta in collaboration with the Institute for, 2026)
This study analyses the influence of brand image, price, and customer satisfaction on customer loyalty among Telkom product users. The research employed purposive sampling with 104 current or former Telkom users as respondents. Data were collected through a questionnaire using Likert scale adapted from the PIRQUAL instrument. Data analysis applied SEM with SmartPLS, including outer and inner model tests for reliability, convergent and discriminant validity, and an assessment of direct and indirect effects. The results show that all constructs met reliability and validity standards, the model demonstrates strong predictive ability for customer satisfaction and loyalty. Findings reveal that brand image is the most dominant factor influencing loyalty, both directly and through satisfaction. While price has a significant impact on customer satisfaction, its influence on loyalty is limited without the presence of other supporting factors. Overall, customer loyalty is more influenced by brand-related perceptions than by functional factors such as price.